2023
DOI: 10.1136/bmjopen-2022-066418
|View full text |Cite
|
Sign up to set email alerts
|

Canadians’ opinions towards COVID-19 data-sharing: a national cross-sectional survey

Abstract: ObjectivesCOVID-19 research has significantly contributed to pandemic response and the enhancement of public health capacity. COVID-19 data collected by provincial/territorial health authorities in Canada are valuable for research advancement yet not readily available to the public, including researchers. To inform developments in public health data-sharing in Canada, we explored Canadians’ opinions of public health authorities sharing deidentified individual-level COVID-19 data publicly.Design/setting/interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Interestingly ( Table 7 ), two studies concluded that older age was associated with a higher willingness to share HD—one focused on medication records for primary purposes 93 and another focused on COVID-19 data for secondary purposes. 99 Those with higher education levels and a positive COVID-19 vaccination status showed higher support for sharing COVID-19 data for secondary uses. 99 Other data-specific factors included societal and self-stigma (in case of sharing non-psychiatric and psychiatric medication among patients with multiple sclerosis), 94 higher levels of satisfaction with the UK's NHS, personal experience of mental illness (sharing mental health illness data), 100 communication about prosocial benefit or social-life-enabling benefit of the app, and higher perceived risk of the disease (in case of sharing COVID-19 infection data to a tracing app).…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly ( Table 7 ), two studies concluded that older age was associated with a higher willingness to share HD—one focused on medication records for primary purposes 93 and another focused on COVID-19 data for secondary purposes. 99 Those with higher education levels and a positive COVID-19 vaccination status showed higher support for sharing COVID-19 data for secondary uses. 99 Other data-specific factors included societal and self-stigma (in case of sharing non-psychiatric and psychiatric medication among patients with multiple sclerosis), 94 higher levels of satisfaction with the UK's NHS, personal experience of mental illness (sharing mental health illness data), 100 communication about prosocial benefit or social-life-enabling benefit of the app, and higher perceived risk of the disease (in case of sharing COVID-19 infection data to a tracing app).…”
Section: Resultsmentioning
confidence: 96%